Flawless [videorecording (DVD)] - Schumacher, Joel, 1939-2020-; De Niro, Robert; Hoffman, Philip Seymour, 1967-2014; Miller, Barry, 1958- (MGM Home Entertainment, 2000)
An ex-cop suffers a stroke and is paralyzed and unable to speak clearly. On the advice of his doctor, he seeks voice lessons from a musically-inclined neighbor, a female impersonator whom he vehemently dislikes.